(untitled) (Medical Research, 2022)
Stress is present in everyday lives and is considered to be the driving force of evolution. Anxiety, chronic worries, panic attacks are the most common consequences of long-term and exhausting stress. The most significant fundamental contribution that is crucial for the development of the modern concept of stress was made by Claude Bernard who proposed the theory that the body is constantly maintaining a stable and well-balanced internal environment or "milieu interieur". Maintaining the internal environment constant Cannon defined as homeostasis and proposed two maintenance mechanisms, through negative feedback from the autonomic nervous system and through sensory organs. Hans Selye proposed stress as a non-specific strain on the body, caused by altered body function followed with release of stress hormones. He called this general adaptation syndrome that had three stages: alarm reaction, initial phase exhibiting “fight or flight” response; resistance, when body is getting used to being stressed and exhaustion when resistance to stress is gradually decreased and collapses. Hans Selye was the first to coin the term “heterostasis” representing a procedure by which a new stable state was achieved by activation of physiological adaptive mechanisms. Lazarus pointed out emotions as an important factor in behavior in response to stress and described an explanation of various reactions to stressors. He emphasizes the process of cognitive assessment as a mediator in dealing with stressors - how a person thinks or evaluates an event in order to understand stress reactions in people. Eustress, considered as a positive stress leads to toned emotions, motivation and focused energy, while distress, negative stress, occurs after prolonged stress that exceeds our ability to deal with. Distress causes anxiety or withdrawal (depression and anxiety), and is accompanied by unpleasant feelings, reduced work ability leading to mental and physical illnesses.